Selected approaches for testing asset pricing models using Polish stock market data - Czapkiewicz, Anna; Skalna, Iwona (Decision Making in Manufacturing and Services, 2014)
The main objective of this paper was to discuss alternative methods for testing the Fama-French (FF) three-factor asset pricing model. The properties of the selected methods were compared in a simulation study. The main stress was put on the behavior of the selected methods for small samples. The parameters used in the simulation study were obtained based on real data coming from the Polish stock market (Warsaw Stock Exchange). Different sample characteristics such as homoscedasticity, conditional heteroscedasticity and autocorrelation as well as heteroscedasticity of the model were tested.